Wilson’s Disease: Current Therapies, Its Controversies, and Potential New Therapeutics - Dias Rima Sutiono; Giardani Syafitri Sudiro (PT. Kalbe Farma Tbk., 2018)
Wilson’s Disease is a rare genetic disorder with the prevalence of 1 in every 30,000 people, due to the mutation of the ATP7B gene responsible for copper metabolism. The mutation causes copper accumulation in the body, especially in the liver and brain, which leads to hepatic, neurological, psychological symptoms. These symptoms, if not treated properly, may lead to death after several years. Several treatments including low copper diet, zinc salts treatment, chelating agents (penicillamine, trientine, ammonium tetrahimiolybdate), and liver transplant are currently available. Severe neurological deterioration and other side effects need new, more efficient, and safer therapeutics. Several new therapeutic agents including 4-phenylbutyrate, curcumin, chelating polymeric beads, and long term metabolic correction have been tested in vitro and in vivo. These new therapeutics may be a potential new treatment with less side effect and greater efficacy for Wilson’s Disease patients.